Evaluasi Total Koloni Bakteri dan Cita Rasa Telur Asin dengan Perlakuan Perendaman Ekstrak Kulit Bawang (Allium ascalonicum) - D. Novia; I. Juliyarsi; P. Andalusia (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2011)
Onion skin is a waste of agricultural products rich with tannin content. The purpose of this study is to determine the effect of soaking salted eggs with the extraction of onion skin (Allium ascalonicum) for water content, pH, bacteria colony, and organoleptic of salted eggs . 200 grains of Anas javanicus eggs duck, 5000 g of brick powder, 1000 g of salt and 2800 g of onion skin were used in this experiment. The experiment was designed in a randomized block design (RBD) with 5 different treatments of soaking salted eggs time in onion extraction, and four different groups of duck eggs as replicates. The treatments of soaking salted eggs in extraction of union skin were control (K); soaking one day (1H); immersion for three days (3H); immersion for 5 days (5H); immersion for 7 days (7H). Variables measured were water content, pH, bacteria colony, and organoleptic of salted eggs product. The results showed that there was no effect of the time of soaking on water content and pH of salted duck egg, while it affect the total bacteria colony and organoleptic significantly. It was concluded that one day of immersion is the best immersion for making salted eggs.